2017
DOI: 10.1109/jlt.2017.2717868
|View full text |Cite
|
Sign up to set email alerts
|

Optical Heterodyne Microvibration Detection Based on All-Fiber Acousto-Optic Superlattice Modulation

Abstract: We propose a configuration of optical heterodyne micro-vibration detection based on an all-fiber acousto-optic superlattice modulation structure that acts as both frequency shifter and reflector, simultaneously. The vibration information within the frequency range between 1 Hz to 150 kHz of a piezoelectric mirror (PZM) has been experimentally measured by using this all-fiber optical heterodyne detection configuration. The minimal measurable vibration amplitude and the resolution are around 0.013 nm and 10 pm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Where R represents the detection coefficient of the PD, where the first two are DC components and the last is millimeter wave component. Finally, the whole system can output the millimeter wave band signal whose frequency is the difference between the two optical signal frequencies after filtering out the DC signal by the band-pass filter (BPF) [27] . The optical heterodyne system is simple in structure and has a higher signal frequency than direct modulation [28] .…”
Section: Optical Heterodynementioning
confidence: 99%
“…Where R represents the detection coefficient of the PD, where the first two are DC components and the last is millimeter wave component. Finally, the whole system can output the millimeter wave band signal whose frequency is the difference between the two optical signal frequencies after filtering out the DC signal by the band-pass filter (BPF) [27] . The optical heterodyne system is simple in structure and has a higher signal frequency than direct modulation [28] .…”
Section: Optical Heterodynementioning
confidence: 99%
“…Laser heterodyne detection (LHD) measures the interference signal between the target echo and the locally oscillating (LO) light, to obtain the frequency, phase, and amplitude information of the target echo and ultimately realize the measurement of the target distance, velocity, vibration, and so on [1,2]. LHD has an advantage over laser direct detection in terms of accuracy and sensitivity in acquiring the multidimensional motion information of a target [3][4][5][6][7]. In LIDAR application scenarios, such as synthetic aperture lidar and advanced remote sensing [8][9][10][11][12][13][14], etc., surface topography undulations of a moving target or atmospheric turbulence can lead to random phase fluctuations at different points in the optical field, thus introducing random phase noise [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The pioneered discovery in 1986 that Kim et al firstly proposed and demonstrated the mode conversion with a frequency shift by a two-mode fiber-based AOMC [43], which has opened a door to novel researches on acousto-optic interactions (AOI) in fibers and various derived components. Among them, the most extensively concerned are tunable filters [51][52][53][54][55][56][57][58][59][60][61][62][63][64], super lattice modulations [65][66][67][68][69], heterodyne vibration detections [70][71][72][73], AOI in photonic crystal fibers (PCFs) [74][75][76][77], wavelength tunable lasers [78][79][80][81][82], ultrafast fiber lasers based on AOMCs [83][84][85][86][87][88][89][90][91][92], vector modes generations [93][94][95]...…”
Section: Introductionmentioning
confidence: 99%
“…Recently, benefit from the new mechanism of the co-effect of acoustic and optical birefringence on the AOMC in an ellipse-core FMF (E-FMF), dynamic mode switching could be demonstrated successfully via frequency shift keying (FSK) technique. The novel AOMC with dynamic mode switching has attracted immense attentions targeting in dynamic optical field tuning for HOM lasers sensing [70][71][72][73] Orthogonal mode switching [107] OAM switching [105] Tunable notch filter [51][52][53][54][55][56][57][58][59][61][62][63][64] MZI tunable filter [60] 2020 Figure 1: The development tree of researches based on acousto-optic (AO) interactions in fibers.…”
Section: Introductionmentioning
confidence: 99%